Multiple lump solutions and their interactions for an integrable nonlinear dispersionless PDE in vector fields - Batool, Tahira; Seadawy, Aly R.; Rizvi, Syed T.R. (Nonlinear Analysis: Modelling and Control, 2023)
In this article, lump solutions, lump with I-kink, lump with II- kink, periodic, multiwaves, rogue waves and several other interactions such as lump interaction with II-kink, interaction between lump, lump with I-kink and periodic, interaction between lump, lump with II-kink and periodic are derived for Pavlov equation by using appropriate transformations. Additionally, we also present 3-dimensional, 2-dimensional and contour graphs for our solutions.